Do Laboratory Results Concerning High-Viscosity Glass-Ionomers versus Amalgam for Tooth Restorations Indicate Similar Effect Direction and Magnitude than that of Controlled Clinical Trials? - A Meta-Epidemiological Study. - Steffen Mickenautsch; Veerasamy Yengopal (PLoS ONE, 2015)
Background A large percentage of evidence concerning dental interventions is based on laboratory research. The apparent wealth of laboratory evidence is sometimes used as basis for clinical inference and recommendations for daily dental practice. In this study two null-hypotheses are tested: whether trial results from laboratory and controlled clinical trials concerning the comparison of high-viscosity glass-ionomer cements (HVGIC) to amalgam for restorations placed in permanent posterior teeth have: (i) similar effect direction and (ii) similar effect magnitude. Methods 7 electronic databases were searched, as well as reference lists. Odds ratios (OR) and Standardised Mean Differences (SMD) with 95% Confidence intervals were computed for extracted dichotomous and continuous data, respectively. Pooled effect estimates for laboratory and clinical data were computed to test for effect direction. Odds ratios were converted into SMDs. SMDs from laboratory and clinical data were statistically compared to test for differences in effect magnitude. The analysed results were further investigated within the context of potential influencing or confounding factors using a Directed acyclic graph. Results Of the accepted eight laboratory and nine clinical trials, 13 and 21 datasets could be extracted, respectively. The pooled results of the laboratory datasets were highly statistically significant in favor of amalgam. No statistically significant differences, between HVGICs and amalgam, were identified for clinical data. For effect magnitude, statistically significant differences between clinical and laboratory trial results were found. Both null-hypotheses were rejected. Conclusion Laboratory results concerning high-viscosity glass-ionomers versus amalgam for tooth restorations do not indicate similar effect direction and magnitude than that of controlled clinical trials.